Effect of variable nitrogen sources on seed yield, seed quality and nutrient uptake of okra (Abelmoschus esculentus) - RANA, RACHNA; BADIYALA, D; GULERIA, GUNJAN (The Indian Journal of Agricultural Sciences, 2018)
During kharif season of 2012 and 2013, a field experiment was conducted at CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur to study the effect of variable nitrogen sources on seed yield, seed quality and nutrient uptake of okra [Abelmoschus esculentus (L.) Moench]. The experiment consisted of seven treatments, viz. 25% N through FYM + 75% N through inorganic fertilizer, 25% N through fortified vermicompost + 75% N through inorganic fertilizer, 25% N through vermicompost + 75% N through inorganic fertilizer, 50% N through FYM + 50% N through inorganic fertilizer, 50% N through fortified vermicompost + 50% N through inorganic fertilizer, 50% N through vermicompost + 50% N through inorganic fertilizer and recommended dose of fertilizers. The result of two years study revealed that the use of 50% N through fortified vermicompost + 50% N through inorganic fertilizer resulted in significantly highest seed yield of 694.4 kg/ha and 745.4 kg/ha during 2012 and 2013, respectively. Significantly higher number of capsules/plant, seeds/capsule and long capsules with the application of 50% N through fortified vermicompost + 50% N through inorganic fertilizer were recorded. Application of 50% N through fortified vermicompost + 50% N through inorganic fertilizer resulted in significantly higher net returns (180.2 × 103 Rupees/ ha/year) and net returns per rupee invested (Rupees 4.91). Moreover, seed quality parameters were also enhanced with the application of 50% N through fortified vermicompost + 50% N through inorganic fertilizer over other treatments.